2020
DOI: 10.1177/1359105320911432
|View full text |Cite
|
Sign up to set email alerts
|

Subjective social status is indirectly associated with short-term smoking cessation through nicotine withdrawal symptoms

Abstract: This study used data collected from a smoking cessation program ( N = 146) to evaluate whether subjective social status was indirectly associated with smoking cessation through nicotine withdrawal symptoms. Findings indicated that subjective social status was indirectly associated with smoking cessation through withdrawal symptoms, specifically through anger and anxiety symptoms. People with lower subjective social status reported more withdrawal symptoms, particularly symptoms related to anger and anxiety, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A study found that people with lower subjective social status had more withdrawal symptoms, especially symptoms related to negative affect (anger, anxiety). 91 There are 2 potential explanations for the high degree of clustering of people who use tobacco products. The first explanation provides a hypothesis for the social reinforcement of smoking behavior, as people with similar personalities and behaviors tend to cluster together.…”
Section: Social Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study found that people with lower subjective social status had more withdrawal symptoms, especially symptoms related to negative affect (anger, anxiety). 91 There are 2 potential explanations for the high degree of clustering of people who use tobacco products. The first explanation provides a hypothesis for the social reinforcement of smoking behavior, as people with similar personalities and behaviors tend to cluster together.…”
Section: Social Factorsmentioning
confidence: 99%
“…A study found that people with lower subjective social status had more withdrawal symptoms, especially symptoms related to negative affect (anger, anxiety). 91 …”
Section: Social Factorsmentioning
confidence: 99%
“…Many of these studies find that, even after objective aspects of SEP such as education, occupation, and income are accounted for, individuals’ perceived position in the social hierarchy is associated with their well-being outcomes. Scholars usually assume that perceived SEP involves some form of social comparison because individuals have to size themselves up against others to learn about their place in the socioeconomic structure (Alexander et al, 2021; Hoebel and Lampert, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the prevalence of tobacco addiction and tobacco-related morbidity and mortality remains disproportionately higher among populations facing significant socioeconomic disadvantage (Cornelius et al, 2022). Socioeconomic-related health disparities in tobacco addiction have consistently linked objective indicators of socioeconomic status (SES; e.g., low educational attainment, low income, unemployment, and poverty level) with increased risk of tobacco use initiation, progression to regular smoking, as well as reduced likelihood of smoking cessation (Alexander et al, 2021;Businelle et al, 2010;CDC, 2009;Hiscock et al, 2012;Kendzor et al, 2012;CDC, 2011). However, an emerging line of research suggests that subjective perceptions of financial strain and/or stress and worries related to one's ability to afford basic necessities may have a more substantial influence on health and smoking behaviors than actual SES (Demakakos et al, 2008;Nobles et al, 2013;Reitzel et al, 2014Reitzel et al, , 2013Ryu & Fan, 2022;Wilkinson et al, 2009).…”
mentioning
confidence: 99%